GOVERNANCE, MANAGEMENT, AND REGULATORY CHALLENGES IN ADOPTING INTERNATIONAL NORMS ON GENETICALLY MODIFIED ORGANISMS CORN POLICY IN INDONESIA - Ratna Istianah; Dinul Fitriadi; Siti Raysa (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
The right to food represents a fundamental component of international human rights as stated in the Universal Declaration of Human Rights (1948), the International Covenant on Economic, Social and Cultural Rights (1966), and the FAO Voluntary Guidelines (2004). Indonesia has integrated these global norms into its national legal framework through Law No. 18/2012 on Food, Government Regulation No. 17/2015 on Food Security and Nutrition, and the National Action Plan for Food and Nutrition 2021–2024. One of the emerging governance challenges lies in the management of genetically modified organisms (GMO), particularly GMO corn. The Indonesian government regulates biosafety and GMO product release through Government Regulation No. 21/2005 and Minister of Agriculture Regulation No. 38/2022. While GMO corn adoption is expected to enhance productivity and national food security, concerns persist regarding biosafety risks, corporate seed control, and the vulnerability of smallholder farmers. This study aims to analyze the degree of international norm adoption into national policies, identify key governance and management obstacles, and propose corrective strategies based on good governance principles. Using a qualitative descriptive approach and policy document analysis, the study reveals gaps between global normative commitments and domestic policy practices, characterized by regulatory overlaps, weak inter-agency coordination, sectoral political dynamics, and institutional capacity limitations. Strengthening inter-sectoral coordination, harmonizing regulations, developing human resources, and expanding public participation are recommended to promote a more equitable and sustainable food governance system in Indonesia.